Hybridity, Reflexivity and Mapping: A Collaborative Ethnography of Postcolonial Gameplay - Lammes, Sybille; Smale, Stephanie de (Open Library of Humanities, 2018)
To date, game studies has largely undertheorized the co-production of postcolonial stories, exploration, and mapping in games. Furthermore, as has been noted before (Carr, 2006), the work that has been done on postcolonialism and play so far often leaves the player out of the equation, even sometimes as a theoretical construct. Yet player experience is crucial to understanding such games, as narratives are not only built on the ‘master’ level of game mechanics, but also through the personal stories players processually (Ash, 2009; Thrift, 2008) develop through their journey of touring and mapping, thereby developing spatial stories (De Certeau, 1984; Jenkins, 2004; Lammes, 2009) that may present us with conflicting spatio-temporal accounts. Through a comparative and collaborative auto-ethnographic analysis of Civilization VI (Sid Meier, 2016) – a turn-based strategy game – we want to push this discussion further and improve our theoretical understanding and analytical purchase of the triad relation between narrative and postcolonialism in games, thereby contributing to the field of postcolonial theory and game studies. Drawing on postcolonial geography, science and technology studies (STS), non-representational theory and game studies, we argue that games, through their playful, explorative and emergent qualities, are a powerful means of rethinking and reimagining colonial (hi)stories in this postcolonial era (Lammes, 2009, 2010) including issues of spatio-temporality, cartography and the hybrid relation between women and machines.
Number: 1
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Humanités numériques; 2-Méthodologie de recherche décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Europe (lieu de production du savoir); 5-Autrice; _Nettoyé